Autonomia jednostki w międzynarodowym prawie biomedycznym - Wnukiewicz-Kozłowska, Agata (E-Wydawnictwo. Prawnicza i Ekonomiczna Biblioteka Cyfrowa. Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2019)
The purpose of the monograph entitled "Individual’s autonomy in international biomedical law" is to present and analyze the legal situation of the patient and physician in the process of making medical decisions under international law perspective in connection with the development of biology, biotechnology and medicine. Beginning with the introduction of the decalogue of rules of conducting biomedical research on human beings set forth in the Nuremberg Code of 1947, with its guiding principle of respect for patient autonomy expressed in the voluntary and informed consent formula for participation in the experiment, international biomedical law is constantly and consistently developing as a specialized branch of international law. An important subject of this law are both patients and doctors. Next to states and international organizations that create and enforce the standards of biomedical law, they are the recipients of rights and duties. The central principle around which international biomedical law is formed is the autonomy of the individual. It is based on the dignity and freedom of every human being. In the medical context it is extremely important because it enables both sides of the doctor-patient relationship to realize the values important to them. On the part of the doctor, it is mainly knowledge and professional experience along with the command to serve human life and health as the highest values in medicine and his/her profession. For the patient, in turn, the essence of autonomy is the ability to independently decide on treatment, including the option to refuse therapy. The autonomy of both entities may interfere with each other. Therefore, the role of law is to strike the balance between the rights and duties of these parties. This is possible in the very process of constructing their competences and powers, as well as by introducing limitations. These limitations reflect classical premises, first of all in the form of the necessity to protect the rights of other people and public health. The analysis of the patient's and doctor's position in international biomedical law leads to several conclusions, of which the two most important ones should be emphasized. First of all, international biomedical law is shaped as a branch of public international law, constituting an element of this system, which means that it operates as a part of a whole with specific rules and norms. The second aspect is the increase of the importance of patient's rights and physician's duties not only in the internal law of states, but also at the international level, taking into account the already adopted and working human rights construction towards respect for the dignity, integrity and identity of the individual in the face of the increasingly advanced and modern biology, biotechnology and medicine. This tendency was clearly articulated in the Convention for the Protection of Human Rights and Dignity of the Human Being in the Application of Biology and Medicine and a very rich soft law created mainly by the WHO, UNESCO, Council of Europe and professional medical organizations.
Keywords: prawo międzynarodowe publiczne; międzynarodowe prawo biomedyczne; prawa człowieka; jednostka; pacjent; lekarz; autonomia; godność; wolność; integralność; świadoma i dobrowolna zgoda; rozwój medycyny; biologii i biotechnologii; kształtowanie linii orzeczniczej; relacja między autonomią lekarza i autonomią pacjenta; system prawa międzynarodowego; fragmentacja prawa międzynarodowego; soft law; bioetyka; deontologia lekarska; odpowiedzialność za naruszenie praw pacjenta